Examining the Virtues of Organisational Citizenship Behaviour (OCB) at an SME - Popovicsné Szilágyi, Zita (International Journal of Engineering and Management Sciences, 2023)
Nowadays, especially in the Eastern region of Hungary, small businesses face an increasing challenge in attracting and retaining a well-qualified workforce that is able to accept and commit to the goals of SMEs. This is due to the promising career prospects offered by foreign-owned large companies locating here. However, if SME employees possess the virtues of organisational citizenship behaviour (OCB), they will develop a stronger commitment to the organisation. The aim of our research was to explore the extent to which the five OCB virtues; sportsmanship, conscientiousness, altruism, politeness and civic virtue are present in a small construction company in Hajdú-Bihar county. Our survey was carried out using a questionnaire method, which was analysed as a function of length of service, education and age. The main findings are that there is a strong correlation between the presence of OCB characteristics and age and length of time spent with the firm.